PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL INKUIRI MELALUI DROSOPHILA VIRTUAL LABORATORY PADA PEMBELAJARAN BIOLOGI SMA MATERI POKOK POLA-POLA HUKUM MENDEL - Prophylia, Marceline; Kardi, Soeparman; Widodo, Wahono (JPPS (Jurnal Penelitian Pendidikan Sains), 2017)
This research is a study of the Development of Teaching and Learning Materials based on Inquiry Model through the Drosophila Virtual Laboratory in an Effort to Improve Student Learning Outcomes in Biology at Senior High School on Topic Learning Patterns of Mendelian Law. The subject of this research is Teaching and Learning Materials. Based on the validators result the whole device is worth and can be applied. Based on the results of the application in the field, it appears that fulfillment of the lesson plan takes place very well. Student activity reaches 100% meaning that all students are active. Completeness results of the study of the students show a very significant change, the average score is 85, which means all students complete the study. From the response of the students, generally they can accept/agree the learning tool developed by inquiry model through Virtual Drosophila Labs. It is an effective and innovative device that can make students more active, help them in improving their learning outcomes of the aspect of the spiritual, social, knowledge, and skills. Based on the results of the study can be concluded that the teaching and learning materials developed in this research is feasible and can be applied to improve student learning outcomes in biology at senior high school on topic learning patterns of Mendelian Law. Penelitian ini adalah penelitian pengembangan perangkat pembelajaran Biologi SMA dengan model inkuiri melalui Drosophila Virtual Laboratory pada Materi Pokok Pola-pola Hukum Mendel. Subyek penelitian ini adalah perangkat pembelajaran. Berdasarkan hasil validasi seluruh perangkat dikategorikan baik dan layak diimplementasikan. Berdasarkan hasil penerapan di lapangan tampak bahwa RPP terlaksana dengan baik. Aktivitas siswa mencapai 100%, yang artinya seluruh siswa bersifat aktif. Ketuntasan hasil belajar siswa menunjukan perubahan yang sangat signifikan, yaitu skor rata-rata 85 yang berarti seluruh siswa tuntas. Dari sisi respon siswa, secara umum mereka dapat menerima/setuju bahwa perangkat pembelajaran yang dikembangkan dengan model inkuiri melalui Virtual Drosophila Labs merupakan perangkat yang efektif dan inovatif, dapat membuat siswa lebih aktif, membantu dalam meningkatkan hasil belajar siswa dari aspek spiritual, sosial, pengetahuan, dan ketrampilan. Berdasarkan hasil penelitian ini dapat disimpulkan bahwa perangkat pembelajaran yang dikembangkan dalam penelitian ini berkategori layak dan dapat diterapkan untuk meningkatkan hasil belajar siswa pada pembelajaran Biologi SMA materi pokok pola-pola Hukum Mendel.